Proses Kreatif Penciptaan Tari Baris Bebek Bingar Bengkala (Bebila) di Desa Bengkala Buleleng - Ni Ketut Ayu Pratini Wulandari; Ida Ayu Trisnawati; I Ketut Sutapa (Jurnal IGEL : Journal Of Dance, 2025)
This article is the result of research related to the creative process of creating the Baris Bebek BingarBengkala (Bebila) dance in Bengkala Buleleng Village, which was created by Ida Ayu Trisnawati in 2016 as atraditional Balinese dance in the form of a line specifically created for the deaf-mute or kolok community in thevillage Bengkala. This dance work indirectly breaks the stigma of society that looks down on people with disabilitiesbecause it has managed to get quite good appreciation. Interestingly, the kolok dancers in their performances are notgiven any code or instructions from anyone at all. They danced like normal dancers usually on stage. It is thedrummers who follow every motion accent that comes out of the dancer's body. The method applied in this study is aqualitative method with reference to the Theory of Creativity and The 4P Theory. The research results obtained show thatthe process of creating the Baris Bebila dance work is a process of the body's journey to find specialties in eachindividual regardless of the shortcomings they have. The process of creating the Baris Bebila dance showsthat dance isa universal language for expression and communication. Dance allows people who cannot speak or hear tocommunicate through movement.Keywords: Baris Bebila Dance, Creative Process, Deaf-Mute/ Kolok